The core aspects of teacher’s book content: An analysis on teacher’s needs - Fahmi Fahmi; Bambang Widi Pratolo; Azwar Abbas (Institute of Advanced Engineering and Science, 2022)
The aspects of the content of teacher’s book received less concern among the teachers, academicians, and researchers. Therefore, the present study was carried out to investigate the core aspects of teacher’s book content based on teachers' needs. Three experienced-teachers from different junior high schools were involved in the present study. The study used a descriptive qualitative method. A need analysis was carried out to obtain the data through semi-structured interviews. The data was collected and analyzed through coding and categorizing techniques based on the questions category. The study found that there were several core aspects needed by the teachers that should be included in a teacher’s book content, namely appearance design/layout, procedures in teaching, material explanation, teaching aids, teaching and learning assessment, time allocation, example of classroom language, and key answers. These aspects are purely based on the analysis on teachers' needs and expectations. The researchers point out that this investigation is fruitful to carry out since it synchronizes the content of the teacher’s book and the needs of the teachers which provide a set of ready-made procedures or proper steps in teaching. The present study strongly supports any researchers to investigate other essential aspects of teacher-textbook’s content for more resourceful content.